POTENTIAL UTILIZATION OF SOLID WASTES FROM TEXTILE INDUSTRY AS A CALORIFIC VALUE ENHANCER WITH MUNICIPAL SOLID WASTE - Christian Kioshi, Kenneth
Textile solid waste is generally known to have high calorific value. However, current refuse derived fuel (RDF) options in Indonesia have not used textile solid waste as the main variable for mass production as stated by National Development Agency (Bappenas) in 2021. This study examines primarily the potential textile solid waste calorific value of textile solid waste of 3 out of 5 major textile industries known as weaving, knitting, and garment industry in Majalaya City with each total industry of 110, 39, and 40 industries respectively and mass of MSW required to fulfill the RDF standard calorific value when mixed with textile solid waste composition as the independent variable. Primary data consists of textile solid waste sampling and waste generation for each of the 3 textile industries (weaving, knitting, and towel garment) resulting in approximately 5.68, 0.83, and 28.1 tons/day respectively, and secondary data consisting of a list of RDF standards such as cement industry standard, SNI 8966:2021, and European standard to add validity whether the potential calorific value of textile solid waste itself can act as an enhancer as the independent variable to increase potential RDF calorific value. In addition, obtaining proximate and calorific value data in the laboratory following the American Society for Testing and Materials (ASTM) and SNI standards known as the following: moisture content (SNI 03-1971-1990), volatile content (ASTM E 897-88-2004), ash and fixed carbon content (ASTM E 830-87-2004), and calorific value (ASTM D 5865) which results , moreover, secondary data consisting of a list of RDF standards such as cement industry standard, SNI 8966:2021, and European standard to add validity whether the potential calorific value of textile solid waste itself can act as an enhancer as the independent variable to increase potential RDF calorific value . Proximate and calorific value analysis reveals that the textile solid waste generated has an average calorific value of 17.19 MJ/kg known to be above minimum required calorific value of each RDF standard. Further data simulation on the MSW mass required for mixing with textile solid waste to fulfill the RDF calorific value standard and specifically chosen cement industry standard with the calorific value minimum requirement is done using data interpolation of mass and calorific value of both MSW and textile solid waste resulting in a MSW to textile solid waste ratio of 1.43 (143-ton MSW to 100-ton textile solid waste). This ratio is used as foundationally applicable to any quantity of textile solid waste when determining the corresponding MSW mass needed to supplement in fulfilling the cement industry RDF standard of 12.55 MJ/kg. As the requirement of RDF calorific value is valid, further research on the potential economic value is done as such by determining an RDF waste flow system which can facilitate industrial textile solid waste and its components resulting to a total capital expenditure (CAPEX) and operational expenditure (OPEX) of approximately Rp3.8 billion and Rp 5.8 billion/year respectively. In addition, a feasibility analysis for a 20- year business plan using net present value (NPV) and benefit cost ratio (BCR) is determined as approximately Rp202 billion and 2.23 respectively showing that a net positive value and BCR > 1 indicates that the project is economically feasible. However, the validity of the economic value requires primary data from existing conditions, which is not available in this research paper.